Measuring the "Poverty Penalty" in the UK. Issue 4 (2nd August 2017) - Purdam, Kingsley; Royston, Sam; Whitham, Graham
Abstract: People with limited financial resources can face additional costs for essential goods and services. This is a challenge for the new British government to address, and a problem that must be reflected in government statistics, say Kingsley Purdam, Sam Royston and Graham Whitham